R&D investments and employment decisions as a function of enterprise size and regional population density before and during COVID-19 - Aarstad, Jarle; Jakobsen, Stig-Erik; Kvitastein, Olav Andreas (Frontiers in Research Metrics and Analytics, 2023)
Norwegian data show that from 2018 to 2020, enterprises in densely populated regions increased R&D investments relative to those in sparsely populated ones, but not from 2016 to 2018. Therefore, COVID-19 likely induced the shift. The findings imply that densely populated regions have become more R&D intensive while sparsely populated ones have become less R&D intensive during the pandemic. Small enterprises increased both R&D investments and employment from 2018 to 2020 relative to large ones. The findings were similar from 2016 to 2018, which rules out COVID-19 as an explanation. Instead, the waves of data indicate a long-term trend where small enterprises increased R&D investments and employment.